2016
DOI: 10.1111/ijsa.12137
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Candidate Social Effectiveness on Assessment Center Performance Ratings: A field study

Abstract: The present research examined the influence of social effectiveness on assessment center (AC) ratings in two samples. We expected different effects of self-monitoring (SM) on different dimension ratings, a positive effect of the ability to identify criteria (ATIC) on the overall AC rating and a moderating effect of the ATIC on the relationship between SM and the dimension rating. Forty-six (Study 1) and 115 (Study 2) applicants participated in ACs in field settings.Across both studies, SM had a negative effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Highhouse et al () showed that self‐monitoring predicted fabricating one's credentials as part of the job search. Finally, self‐monitoring was negatively associated with integrity ratings in assessment centers (Leugnerova, Vaculik, & Prochazka, ). To summarize, self‐monitoring is positively related to deception, which may partly explain their success in interviews.…”
Section: Examination Of Outcomes Of Self‐monitoringmentioning
confidence: 99%
“…Highhouse et al () showed that self‐monitoring predicted fabricating one's credentials as part of the job search. Finally, self‐monitoring was negatively associated with integrity ratings in assessment centers (Leugnerova, Vaculik, & Prochazka, ). To summarize, self‐monitoring is positively related to deception, which may partly explain their success in interviews.…”
Section: Examination Of Outcomes Of Self‐monitoringmentioning
confidence: 99%
“…For example, researchers have argued that self-monitoring can increase deception and faking behaviors (Kudret et al, 2019;Levashina and Campion, 2007;Hogue et al, 2013). Furthermore, self-monitoring can decrease an individual's integrity ratings (Leugnerova et al, 2016). Furthermore, self-monitoring allows individuals to engage in misrepresentations of fit, intending to obtain desirable rewards (Kudret et al, 2019).…”
Section: Jstp 333mentioning
confidence: 99%
“…, 2013). Furthermore, self-monitoring can decrease an individual's integrity ratings (Leugnerova et al. , 2016).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%